Leadership Lessons from Bhagavad Gita - USHA JAISWAL; KARANAM N. RAO (Dr. Chinmay Pandya, 2014)
There has been a flurry of activity in management literature for developing management theories for the last one and half century. People, in general, tend to assume that globally renowned companies adopt the best managerial practices and the management theories of the West are the best worthy of emulation by the Eastern counterparts. In the backdrop of crumbling communist concepts and the near failure of capitalistic models, especially after the fall of Lehman Brothers in USA, scholars have begun to perceive the hollowness of those models and turned their attention to the ancient wisdom of oriental countries.  Leadership is having greater significance in managing an organization. Leaders are the persons who motivate and build the morale of the followers in achieving organizational goals to newer heights. Notwithstanding the prevalence of plethora of literature on leadership from the Western management perspective, scholars have begun to take a relook at ancient Indian scriptures which have valuable lessons in the area of leadership. In Bhagavad Gita, Lord Krishna acted as a role model and imparted great lessons of leadership to Arjuna. An attempt is made in this article to draw leadership lessons from Gita which inspired the people from time immemorial.